PEMBERIAN ABDOMINAL STRETCHING EXERCISE PADA TINGKAT NYERI HAID REMAJA DI SMA NEGERI 2 KUTA - Dewi, Asia; Yunita Sari, Dian; Prihandhani , Sherlyna; Sukriyanti, Ari; Asia Dewi, Ni Nyoman (STIKES Permata Nusantara Cianjur, 2024)
Increased production of prostaglandins during menstruation can result in menstrual pain, namely pain in the lower abdomen or waist area. Therapy that can overcome menstrual pain is abdominal stretching exercise, where this therapy can increase relaxation, muscle strength, flexibility, and increase endorphin levels, thereby reducing menstrual pain. The aim of this research is to determine the effect of abdominal stretching exercise on menstrual pain in adolescents. This research used a pre-experimental design with a one group pretest posttest approach with a sample size of 50 people using a purposive sampling technique. This research instrument uses the VRS (Verbal Rating Scale) questionnaire. Data were analyzed using the Paired Sample T-Test. The results of the study showed that before being given treatment, the 50 respondents got a mean of 2.48 with an SD of 0.677, including the medium category. After being given treatment, a mean of 1.72 was obtained with an SD of 0.671 in the mild category. The results of data analysis in this study obtained a p value of 0.000. It can be concluded that there is an influence of abdominal stretching exercise on menstrual pain in teenagers at SMA Negeri 2 North Kuta.